Invigorasi Benih Merbau Melalui Teknik Matriconditioning dan Osmoconditioning - Anwar, Arniana; Agatha Maturbongs; Muh. Shofi (Jurnal Hutan dan Masyarakat, 2023)
Merbau is a type of tree whose wood is classified as durable with durable class I-II and strong class I-II. Because of this durable and strong class, merbau wood is widely used in industry. This research was conducted with the aim of testing the effect of invigorating merbau seeds using matriconditioning and osmoconditioning methods. The study was conducted using a completely randomized design (CRD) with 6 levels of treatment, namely control, sawdust, husk charcoal, PEG, NaCl and KNO3. The research data were tested using ANOVA and Duncan's follow-up test. The results of the study. The results showed that invigoration treatment could increase the viability of merbau seeds on the observed variables of root length, height, and number of leaves. Of all the invigoration treatments, the best material in increasing the viability of soybean seeds was the matriconditioning treatment using sawdust.